Strategi pengembangan dan strategi promosi dalam mengembangkan Desa Wisata Situ Tunggilis - Sephia Putri Utami; Rini Wijayanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research was conducted using a qualitative approach. The data is obtained through observation, interviews, and documentation the steps for data analysis include data collection, data reduction, data presentation, and drawing conclusions. The purpose of conducting the research is to find out the development strategy and promotion strategy in the tourist village of situ Tunggilis, Bogor district run by Bumdes Situsari. Based on the research results obtained, the steps that must be carried out are ways to develop so as to increase the interest of visitors, such as holding events, forms of promotion, and big events, namely competitions between other villages. Those are distributed through internet forums, for example, Instagram and internet websites.